Sámi Teacher Education or Teacher Education for Sámi Students? Central Cornerstones in Sámi Teacher Education - Nutti, Ylva Jannok (Springer International Publishing, 2023)
Abstract Sámi teacher education programs are core programs at the Sámi University of Applied Sciences, and have been since the establishment of the institution. Sámi teacher education programmes involve flexible teaching methods including online teaching, teaching at gatherings and through practicum periods at early childhood centres and primary schools. The aim of this chapter is to discuss Sámi teacher education as Indigenous higher education, in order to explore the cornerstones of Sámi teacher education. The method used in the present study combines content analyses and a narrative approach. Content analysis is a research tool used to analyse the official documents for teacher education programmes and programme syllabi at Sámi University of Applied Sciences. The narrative approach was selected in order to use personal experiences from Sámi teacher education. As an analytical tool the model of Madden’s (2015) pedagogical pathways in Indigenous teacher education were used. The pathways are learning from traditional Indigenous modes of teaching, pedagogy for decolonizing, Indigenous and antiracist education, and Indigenous and placed-based education. Traditions, traditional knowledge and traditional models of teaching, together with language, are central in Sámi teacher education. Sámi teacher education could also be viewed in connection to placed-based education. Decolonizing is part of the educators’ work to transform and implement traditional knowledge and culture-based teaching perspectives, and in educators’ work to deconstruct culture, history and Indigenous identity. The term “colonial” is not used explicitly. However even if the term is not present, colonialism is indirectly visible. The antiracist education is less visible. All the pathways are visible in Sámi teacher education, but to visualise in Sámi teacher education the cornerstones, the metaphor of the lávvu and three caggi , or poles, is used and the caggit are, in the Sámi language, árbediehtu , and girjás searvelatnja.